Variability of heatwaves across Vietnam in recent decades - Pham Thi, Ly; Pham Thanh, Ha; Phan Van, Tan; Vu Thuan, Yen (Vietnam Journal of Earth Sciences, 2023)
There have been several studies on heatwaves (HW) in Vietnam but they all focused on an individual heatwave characteristic. A comprehensive understanding of heat waves is crucial for effective research on their impacts and for making plans for climate change mitigation and adaptation strategies in the country. This study investigates the spatial variability and changing trends in heatwave characteristics across the climatic sub-regions of Vietnam. The analysis is based on the observed daily maximum temperature (Tx) recorded at 144 meteorological stations in the period of 1980-2018. HW is identified using a relative threshold, which is the local 90th percentile of Tx within 183 days during the summer (1st April - 30th September). Results showed that: (1) The threshold values used to determine HW events varied among sub-regions and stations due to their geographical locations; (2) Across the country, HWs were observed to be more frequent, intense, severe, and longer-lasting in the North Delta and North Central sub-regions compared to others; (3) Over recent decades, both the frequency and severity of HWs have significantly increased across Vietnam, particularly in the North-Delta and North Central sub-regions. However, the changing trends in HW duration and intensity remain unclear.